# Answer on Trigonometry Question for Kristen Woods

Question #20717

Find and simplify a) f(a), b) f(a + h) and f(a+h)-f(a) / h , h≠0 using the given function.

f(x)=x^2-2x+3

f(x)=x^2-2x+3

Expert's answer

a)f(a)=a^2-2a+3

b)f(a+h)=(a+h)^2-2(a+h)+3=a^2+2ah+h^2-2a-2h+3;

f(a+h)-f(a) / h=a^2+2ah+h^2-2a-2h+3-(a^2-2a+3)/h;

b)f(a+h)=(a+h)^2-2(a+h)+3=a^2+2ah+h^2-2a-2h+3;

f(a+h)-f(a) / h=a^2+2ah+h^2-2a-2h+3-(a^2-2a+3)/h;

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment